Promoting lateral bud growth in sweet potato (Ipomoea batatas) - Valeur, Johan (2021)
Sweet potato (Ipomea batatas) is an important crop grown worldwide with a rising interest in production in Europe and Sweden. Swedish producers are looking for ways to grow the crop but are facing problems because of low-quality slips from import which leads to a non-profitable production. This inadequate supply becomes a bottleneck for Swedish farmers. A Swedish propagation of slips would be beneficial to Swedish growers but in order to make such a production effective a solution to break the sweet potato's strong apical dominance is needed. Apical dominance is mainly controlled by auxin supply from the apical meristem. Cytokinin is a phytohormone that promotes lateral bud growth and can therefore also be used to aid the breaking of apical dominance. Although a lot is known about apical dominance there are a lot of unknown factors playing into how it is truly controlled. Coconut water (CW) is a natural, safe and organic biostimulant with enough phytohormones to affect other plants. An experiment was conducted where cuttings of sweet potato rooted in pumice stone and sprayed with a synthetic cytokinin (BAP) or a 20% dilution of CW in order to stimulate lateral bud growth. A control group without any treatment was also made. Every cutting in the experiment had its apex bud removed in order to cut off the main auxin supply. The results showed a 27% higher rate of stimulated lateral buds with BAP treatment and a 20% higher rate with the CW treatment compared to the cuttings without any treatment. The study is too small to prove a correlation but it’s enough to show an indication that these biostimulants might stimulate later bud growth. This indication can be used to motivate a study on a bigger scale.